Into the Pyramids - Foster, Mark.; Burrows, Phillip (Oxford : Oxford University Press, 1998)
Anna is on holiday in Egypt with her mother and Lucretia, her cat. One day they visit the pyramids, and Lucretia becomes a star in a cat food advertisement.
Keywords: Pyramids -- Fiction; Egypt -- Fiction